Applying Pickering Emulsions Stabilized by Octenylsuccinylated Starch and Gum Arabic As Lutein Carriers to Improve Its Stability. (7th June 2021) - Zhang, Yanqi; Li, Songnan; Kong, Lingyan; Tan, Libo
Abstract: Objectives: Lutein is a natural carotenoid commonly found in dark leafy vegetables such as kale and spinach. It cannot be synthesized de novo in animals and therefore must be obtained from diet. In human body, lutein is a potent antioxidant that is mainly accumulated in the eye and can protect eye from blue-initiated light damage. However, the poor stability and bioavailability of lutein limit its application as a nutraceutical in food formulation. In this study, we explored the use of Pickering emulsions, the oil-water interface of which is stabilized by colloidal particles, to encapsulate lutein. The macroscopic stability of the Pickering emulsions stabilized by octenylsuccinylated (OS) starch and gum Arabic (GA), and various oil volume fractions (Φ) was measured during storage. Methods: Pickering emulsions were prepared using three types of OS starch and three types of GA. The aqueous dispersions of these colloidal particles were mixed with corn oil at various Φ at 10%, 30%, 50%, 70%, and 90% using a homogenizer at 20, 000 rpm for 2 mins. Emulsions were sealed in a glass tube and were stored for 28 days to evaluate the stability. Lutein Pickering emulsion was made by dissolving lutein sample (30% in olive oil) in corn oil (0.4%, w/v), and then homogenized with 30% (w/v) OS starch at 50% Φ. Results: After 28 d of storage, 30% OS starch-based Pickering emulsions showed distinct phase separation when Φ was at or below 30% and at 90%. Emulsions with Φ of 50% and 70% were stable but semi-mobile, which could be regarded as Pickering gels. The 10% OS starch was able to stabilize the emulsions within a wider range of Φ (from 10% to 70%), while the oil off showed at 90% Φ. A similar trend was noted in all three types of OS starch that emulsion without layer separation was observed at 50% - 70% Φ. Two types of GA successfully emulsified the oil. The optimal Φ range (50% - 70%) was similar to that of OS starch, while emulsions with 90% Φ showed a large oil phase separated. Lutein carried by OS starch at 50% Φ did not show any observable layer separation after one-week storage. Conclusions: Pickering emulsions were successfully prepared using OS starch and gum Arabic at high Φ ranging from 50% - 70%. Further study will be conducted to investigate the physicochemical characteristics of the lutein-loaded Pickering emulsions and their stability and bioavailability. Funding Sources: University ORED Small Grant Program.